Feliz new year, Ava Gabriela! - Alessandri, Alexandra (Albert Whitman & Company, 2020)
Ava Gabriela is excited to celebrate the New Year with her extended family in Colombia, but being around her loud relatives in an unfamiliar place makes her shy and quiet. Includes author's note and glossary of Spanish words.